Training and Evaluation of Communication Skills - Pyke, S. W.; Neely, C. A. (Canadian Journal of Counselling and Psychotherapy, 2012)
Two programmes, both of which were aimed at more effectiveperformance in small group discussion, were compared. The first approachconsisted of skill training while the second approach, an enrichedprogramme, combined the skill training with a programmed notebook. Bothtraining groups rated themselves as significantly more improved than ano-training control group which showed a slight decrease in self-ratings.The enriched-programme students rated themselves as having improvedsignificantly more than did those given the standard skill training. Thegroup members were also rated by their teachers, outside judges, andtheir peers in the programme. These criterion measures showed both traininggroups more improved than the control group, but the training groupsdid not differ significantly.